POLITIK HUKUM SUMBER DAYA AIR DI ERA GLOBALISASI - Agus Surachman (JURNAL HUKUM DE'RECHTSSTAAT, 2017)
Great mercy and infinite value has been given by God for the creatures on earth, one of which is water, water is basic need for humans because water is the source of life for all living things. Water should be used excessively let alone become a commodity economics without limits, because the water supply is limited, but people often use them without limit, greed and lust enrich themselves lead to exploration of a large scale that makes the damage and loss of balance of natural resources. Globalization has swept across the world, insulation-partition the country into a vague, with free trade seemed about the welfare of the world, though many will doubt it. Britain exit (Brexit) case and the election of Donald Trump as the new President of the United States is reason to question the success of globalization. For that legal arrangements of water resources or the so called “constitution of water resources“, that the law governing resources must not conflict with article 33 paragraph 3 of  the 1945 constitution, said, “the resources of the earth’s natural land, water and natural resources contained therein controlled by the state for the welfare of the people“. Means that water should not be controlled by private for trade to seek maximize profit.